Effects on Inter-Personal Memory of Dancing in Time with Others - Woolhouse, Matthew H.; Tidhar, Dan; Cross, Ian (Frontiers in Psychology, 2016)
We report an experiment investigating whether dancing to the same music enhances recall of person-related memory targets. The experiment used 40 dancers (all of whom were unaware of the experiment’s aim), two-channel silent-disco radio headphones, a marked-up dance floor, two types of music, and memory targets (sash colors and symbols). In each trial, 10 dancers wore radio headphones and one of four different colored sashes, half of which carried cat symbols. Using silent-disco technology, one type of music was surreptitiously transmitted to half the dancers, while music at a different tempo was transmitted to the remaining dancers. Pre-experiment, the dancers’ faces were photographed. Post-experiment, each dancer was presented with the photographs of the other dancers and asked to recall their memory targets. Results showed that same-music dancing significantly enhanced memory for sash color and sash symbol. Our findings are discussed in light of recent eye-movement research that showed significantly increased gaze durations for people observing music-dance synchrony versus music-dance asynchrony, and in relation to current literature on interpersonal entrainment, group cohesion, and social bonding.